Antihyperglycemic and hypoglycemic effects of the flavonoids-rich fraction of Tinospora crispa (L.) Miers ex Hook. F & Thomson (Family Menispermaceae) stem extracts on streptozotocin-nicotanamide-induced diabetic sprague-dawley rats - Pinlac, Vienne D.; Tan, Jarvin Enosh T.
Diabetes mellitus (DM), a disease characterized by a progressively high blood glucose levels, continues to pose a high burden of disease across countries. This study aims to determine the acute antihyperglycemic effects of flavonoid rich of fractions of T. crispa on streptozotocin-nicotinamide-induce diabetic Sprague Dawley rats, as well as to characterize the fractions in term of TLC profile, flavonoid content, and a-glucosidase inhibition. Phytochemical test showed the presence of flavonoids in the chloroform and ethyl-acetate fractions, and TLC and flavonoid content determination showed that ethyl-acetate was relatively more flavonoid-rich fraction. The inhibition of a-glucosidase by the ethyl-acetate fraction make it a possible mechanisms of antidiabetic action: however, there was no statistically significant anti hyperglycemic effect of the fraction (50mg/kg) on diabetic rats compared to negative control as determined by the Kruskal-Wallis equality of populations test (p=0.0794). The same dose was statistically confirmed to not produce hypoglycemia in nondiabetic rats compare to a negative control as shown by post-hoc Dunn's pairwise comparison test (p=0.0109). It is recommended for the improvement of this study that the sample size and streptozotocin dose be increased, and long-term studies of the antihyperglycemic effect of the flavonoid-rich fraction of T. crispa be done. If the latter proves to be successful, purification of the flavonoid-rich fraction may be done to be tested on diabetic rats and its mechanism of antidiabetic actions be determined.
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, 2016.